Meta-Analysis of RAGE Gene Polymorphism and Coronary Heart Disease Risk - Wang, Jun; Zou, Lianjiang; Song, Zhigang; Lang, Xilong; Huang, Shengdong; Lu, Fanglin; Han, Lin; Xu, Zhiyun (PLOS ONE, 2012)
Background Recent data from human and animal studies have shown an upregulated expression of advanced glycosylation end product–specific receptor (RAGE) in human atherosclerotic plaques 1 and in retina, messangial, and aortic vessels, suggesting an important role of RAGE in the pathogenesis of atherothrombotic diseases. In the past few years, the relationship between RAGE polymorphisms (−429T/C, −374T/A, and G82S) and coronary heart disease (CHD) has been reported in various ethnic groups; however, these studies have yielded contradictory results. Methods PubMed, ISI web of science, EMBASE and the Chinese National Knowledge Infrastructure databases were systematically searched to identify relevant studies. Data were abstracted independently by two reviewers. A meta-analysis was performed to examine the association between RAGE polymorphisms and susceptibility to CHD. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated. Results A total of 17 studies including 4343 patients and 5402 controls were involved in this meta-analysis. Overall, no significant results were observed for −429T/C (OR = 1.01, 95% CI: 0.92–1.12, P = 0.78), −374T/A (OR = 1.11, 95% CI: 0.98–1.26, P = 0.09) and G82S (OR = 1.12, 95% CI: 0.86–1.45, P = 0.41) polymorphism. In the stratified analyses according to ethnicity, sample size, CHD endpoint and Hardy-Weinberg status, no evidence of any gene-disease association was obtained. Conclusions This meta-analysis demonstrates that there is no association between the RAGE −429T/C, −374T/A and G82S polymorphisms and CHD.